Pengembangan Business Model Canvas bagi Usaha Kecil Triple 3 Music Bandung - Muhammad Iffan (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2022)
In the current digital era, business actors need new strategies to survive in business competition, one of which is by following the development of e-commerce in order to expand the market. Triple 3 Music Bandung is a small business engaged in selling musical instruments and podcasts. The aim of this article was to convey understanding to Triple 3 Music Bandung and other parties about the business development. The method chosen in this Community Service activity was to conduct interviews with the owner of Triple 3 Music Bandung and make observations on these businesses in order to determine business development strategies using Business Model Canvas analysis. The result of this activity is the proposed of a new strategy that can be implemented in the development of the Triple 3 Music Bandung business based on the nine elements in the Business Model Canvas. The business strategy that has been implemented by the business owner of Triple 3 Music Bandung is quite good, however, it is necessary to develop a business strategy to maximize potential. It is hoped that with the new business strategy, Triple 3 Music Bandung can strengthen its market position and can increase its competitive advantage in competition with similar businesses so as to improve business performance. Keywords: Business Model Canvas, Small Enterprise